Haplotype analysis of field collected aedes albopictus from Taman Bukit Kinrara, Selangor using the Nadh Dehydrogenase Subunit 5 (ND5) marker / Nor Adira Abdul Khalid - Abdul Khalid, Nor Adira (2016)
Studies examining the population genetics structure of Ae. albopictus based on mitochondrial DNA ND5 marker has not been elucidated at the local settings, despite its importance. Hence, this study was conducted to evaluate the intrapopulation and inter population genetic diversity among Ae. albopictus from Taman Bukit Kinrara, Selangor, a dengue cluster areas in Malaysia using a mitochondrial DNA marker. The genomic DNA of ten individual adult female Ae. albopictus mosquitoes and ten USM laboratory strains (USM LS)was extracted and analysed for DNA polymorphism based on the mitochondrial ND5 marker. 450 bp of amplified PCR products was obtained and sequenced. BLAST analysis showed high similarities with reference sequences from NCBI Gen Bank. Subsequently, the multiple nucleotide sequences were aligned using ClustaIX2.l. Haplotype network was constructed using TCS network in PopART software. Haplotypes generated was analyzed using DNaSP. Our findings revealed that Ae. albopictus population from Taman Bukit Kinrara, Selangor are genetically related at intra population and inter population levels with low genetic variation with Hd values of0.4368 and 0.5869 respectively. This study highlights the generation of 11 haplotypes from 49 sequences at 11 different polymorphic sites. The data obtained from this study may provides new fundamental knowledge regarding the genetic structure of local Ae. albopictus that could be utilised in forthcoming studies.